Digital Tools in Language Education: Boosting Listening Skills with Edpuzzle for High School Students - Kholid, M. Fikri Nugraha; Kurniawati, Dewi; Nadila, Aulia Ulva Devi (LinguaEducare: Journal of English and Linguistic Studies, 2024)
This research investigated the impact of the Edpuzzle application on the listening skills of eleventh-grade students at SMAN 1 Sekincau, Lampung Barat. The study aimed to assess whether using Edpuzzle as a digital tool could significantly enhance students' listening comprehension compared to traditional methods. A quasi-experimental design with a pre-test and post-test approach was employed. Two groups were involved: an experimental group that used Edpuzzle for listening practice and a control group that received conventional listening instruction. Pre-tests and post-tests were conducted over six weeks to measure improvements in listening skills, focusing on understanding the main idea, identifying details, and making inferences. Data were analyzed using SPSS version 26, with an independent samples t-test comparing the scores of both groups. Results showed a significant improvement in the experimental group’s listening skills, confirming Edpuzzle's effectiveness in enhancing comprehension. The findings suggest that digital tools like Edpuzzle provide an interactive learning experience, allowing students to learn at their own pace and receive immediate feedback, crucial for developing listening skills. The study implies that educators should integrate digital tools like Edpuzzle into teaching strategies to promote active learning and improve listening skills. It highlights the benefits of combining traditional methods with digital innovations to create more engaging and effective language learning environments. Future research should examine the long-term effects of digital tools in language education and their impact on other language skills.